Long-Term Variation in Wintertime Atmospheric Diffusion Conditions Over the Sichuan Basin - Wang, Guoyin; Leng, Wennan; Jiang, Shaojing; Cao, Bangjun (Frontiers in Environmental Science, 2021)
Atmospheric diffusion is one of the factors affecting local air quality, dominating the evolution of air pollution episodes. Previous work has emphasized the unfavorable diffusion conditions in the Sichuan Basin resulting from its complex terrain. However, the recent spatiotemporal variation in atmospheric diffusion conditions in the basin and their effects on local air quality remain unclear. Based on the wind speed, boundary layer height, vertical potential temperature difference of ERA5 analysis, two independent metrics containing information on horizontal and vertical diffusion ability, i.e., ventilation coefficient (VE) and the air stagnant conditions (ASI), are involved to indicate wintertime atmospheric diffusion conditions in the basin. Both VE and ASI reveal a decrease tendency of atmospheric diffusion condition from the northwestern portion of the basin to the southeast. In terms of the long-term variation in diffusion conditions, VE showed a broader increasing trend from 1979 to 2019, with a distinct increase in the western region. In contrast, the occurrence of air stagnation events has declined -3~-6%/decade in the basin, more significantly over the western basin. Both the increase in VE and the decrease in air stagnation frequency indicate the improvement of atmospheric diffusion conditions in the Sichuan Basin from 1979 to 2019, which mitigates the effects of air pollutant emissions to some extent. The enhancement of diffusion conditions is due to the improvement of vertical diffusion conditions. The lowest seasonal PM2.5 concentrations occur in the northwestern basin, where VE is highest and ASI is lowest. Atmospheric diffusion conditions can explain approximately 25%~50% of the interannual variation in PM2.5 concentrations in Chengdu.